Family Support as a Determinant of Non-Communicable Disease Integrated Service Post Utilization Behavior - Amalia, Aina Shofi Salsabila Nur; Rahmatika, Nanda Tri; Lestari, Saptandia Wulan Cahyaning; Adyatma, Rangga Gama (FORIKES, 2026)
Non-Communicable Diseases (NCDs) increasingly affect not only the elderly but also individuals of productive age (15–59 years). The Integrated Development Post for Non-Communicable Diseases (Posbindu PTM) serves as a community-based strategy for early detection and monitoring of NCD risk factors. This study aimed to analyze factors associated with the utilization behavior of Posbindu PTM services. A quantitative cross-sectional design was employed, involving 68 respondents selected through simple random sampling. The questionnaire used had been tested for validity and reliability. Data were analyzed descriptively and inferentially using the Chi-square test. The results showed no significant association between education, occupation, knowledge, attitudes, availability of facilities, access to Posbindu PTM, and cadre support with utilization behavior. However, a significant association was found between family support and the utilization of Posbindu PTM services. As conclusion, family support plays an important role in encouraging individuals to actively utilize Posbindu PTM services. Comprehensive education targeting families is therefore needed to increase awareness of the importance of utilizing Posbindu PTM services.Keywords: non-communicable diseases; health service utilization behavior; the integrated development post for non-communicable diseases